Prevalence of pulmonary dysfunction in patients with beta thalassemia major: a systematic review and meta-analysis - Amar Taksande; Yash Dalal; Himanshi Jindal; Taksande Bharati (Indonesian Pediatric Society, 2022)
Background Many studies have been conducted on heart, liver, and endocrine abnormalities in thalassemia; however, studies on pulmonary dysfunction (PD) have been limited. Previous studies on the prevalence of restrictive lung disease (RLD) and obstructive lung disease (OLD) in Î²-thalassemia major patients have lacked agreement. Objective To assess the prevalence of PD in Î²-thalassemia major patients by systematic review of the literature and meta-analysis. Methods We searched Cochrane library, PubMed, Web of Science, MEDLINE, Scopus, and Embase for relevant articles. Articles were selected according to the inclusion criteria and data were extracted. The primary outcome was prevalence of pulmonary dysfunction in Î²-thalassemia major with 95% confidence interval (95%CI). Subgroup analyses were applied to explore the prevalence in different age groups, regions, and serum ferritin levels. Sensitivity analysis and publication bias assessment were also conducted. Results A total of 37 studies comprising 1,467 cases were included in this analysis. Pulmonary dysfunction was present in 64.7% (95%CI 57.6 to 71.1) of cases. The pooled prevalence of RLD (44.9%) was higher than that of OLD (7.6%) and diffusion impairment (DI) (35.6%). Subgroup analysis revealed that the region with the highest pooled prevalence of PD was the Americas (75.2%). The highest prevalence of RLD and DI was found in Asia (48.2% and 44.6%, respectively) and that of OLD in Europe (9.7%). Sensitivity analysis showed that the pooled results were robust. Conclusion A high prevalence of pulmonary dysfunction, mainly RLD rather than OLD, was detected in Î²-thalassemia major patients.